Impact of Extracorporeal Membrane Oxygenation (ECMO) on Serum Concentrations of Cefepime - Christopher J. Destache; Raul Isern; Dorothy Kenny; Rima El-Herte; Robert Plambeck; Catherine Palmer; Brent S. Inouye; Maura Wong; E. Jeffrey North; Mariaelena Roman Sotelo; Manasa Velagapudi (Antibiotics)
ECMO is becoming widely used as a life-saving measure for critically ill patients. However, there is limited data on pharmacokinetics and the dosing of beta-lactam antibiotics in ECMO. In this study, we evaluated the serum concentrations of cefepime in patients on ECMO to determine the impact of ECMO circuitry and to guide therapeutic dosing. Methods: Patients 19 years or older admitted to the ICU, treated with ECMO and beta-lactam antibiotics for presumed or documented infection, were enrolled. Three blood samples (peak, midpoint, trough) were obtained before ECMO (pre-ECMO) and during ECMO (intra-ECMO) at a steady state. Results: Eight patients met inclusion criteria; six received cefepime. All patients were male. Average ± SD age was 45.8 ± 14.7. Four patients received ECMO for severe SARS-CoV-2 infection, and one each for Pneumocystis pneumonia and influenza A infection. Mean ± SD APACHE II and SOFA scores prior to ECMO were 24.6 ± 7.1 and 11.0 ± 3.9, respectively. All but one of the patients received venovenous (VV) ECMO. Cefepime 1 g every 6 h intravenously over 2 min was administered to all patients before and during ECMO. Cefepime concentrations were fit to non-compartment analysis (NCA) and area under the serum concentration–time curve averaged ± SE 211.9 ± 29.6 pre-ECMO and 329.6 ± 32.3 mg*h/L intra-ECMO, p = 0.023. No patients displayed signs of cefepime neurotoxicity. Patients received ECMO for 43.1± 30 days. All patients expired. Cefepime dosed at 1 g every 6 h intravenously appears to achieve therapeutic levels for critically ill patients on ECMO.